Identifying and prioritizing strategies for comprehensive liver cancer control in Asia - Bridges John FP; Gallego Gisselle; Kudo Masatoshi; Okita Kiwamu; Han Kwang-Hyub; Ye Sheng-Long; Blauvelt Barri M (BMC, 2011)
Abstract Background Liver cancer is both common and burdensome in Asia. Effective liver cancer control, however, is hindered by a complex etiology and a lack of coordination across clinical disciplines. We sought to identify strategies for inclusion in a comprehensive liver cancer control for Asia and to compare qualitative and quantitative methods for prioritization. Methods Qualitative interviews (N = 20) with international liver cancer experts were used to identify strategies using Interpretative Phenomenological Analysis and to formulate an initial prioritization through frequency analysis. Conjoint analysis, a quantitative stated-preference method, was then applied among Asian liver cancer experts (N = 20) who completed 12 choice tasks that divided these strategies into two mutually exclusive and exhaustive subsets. Respondents' preferred plan was the primary outcome in a choice model, estimated using ordinary least squares (OLS) and logistic regression. Priorities were then compared using Spearman's Rho. Results Eleven strategies were identified: Access to treatments; Centers of excellence; Clinical education; Measuring social burden; Monitoring of at-risk populations; Multidisciplinary management; National guidelines; Public awareness; Research infrastructure; Risk-assessment and referral; and Transplantation infrastructure. Qualitative frequency analysis indicated that Risk-assessment and referral (85%), National guidelines (80%) and Monitoring of at-risk populations (80%) received the highest priority, while conjoint analysis pointed to Monitoring of at-risk populations (p < 0.001), Centers of excellence (p = 0.002), and Access to treatments (p = 0.004) as priorities, while Risk-assessment and referral was the lowest priority (p = 0.645). We find moderate concordance between the qualitative and quantitative methods (rho = 0.20), albeit insignificant (p = 0.554), and a strong concordance between the OLS and logistic regressions (rho = 0.979; p < 0.0001). Conclusions Identified strategies can be conceptualized as the ABCs of comprehensive liver cancer control as they focus on Antecedents, Better care and Connections within a national strategy. Some concordance was found between the qualitative and quantitative methods (e.g. Monitoring of at-risk populations), but substantial differences were also identified (e.g. qualitative methods gave highest priority to risk-assessment and referral, but it was the lowest for the quantitative methods), which may be attributed to differences between the methods and study populations, and potential framing effects in choice tasks. Continued research will provide more generalizable estimates of priorities and account for variation across stakeholders and countries.